2013
DOI: 10.1111/jne.12086
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐Like Peptide‐1 Receptor Agonist Administration Suppresses Both Water and Saline Intake in Rats

Abstract: Glucagon-like peptide-1 (GLP-1) plays an important role in energy homeostasis. Injections of GLP-1 receptor (GLP-1R) agonists suppress food intake, and endogenous GLP-1 is released when nutrients enter the gut. There is also growing evidence that the GLP-1 system is involved in the regulation of body fluid homeostasis. GLP-1R agonists suppress water intake independent of their effects on food intake. It is unknown, however, whether this suppressive effect of GLP-1R agonists extends to saline intake. Accordingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Moreover, we used lower doses than those causing a taste aversion (Kanoski et al ), and we followed up the acute studies with repeated administration of liraglutide, a design with documented tolerance for nausea. This is further substantiated by the findings that liraglutide, in contrast to Ex4, does not condition a taste avoidance to saccharine in mice (McKay & Daniels ).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, we used lower doses than those causing a taste aversion (Kanoski et al ), and we followed up the acute studies with repeated administration of liraglutide, a design with documented tolerance for nausea. This is further substantiated by the findings that liraglutide, in contrast to Ex4, does not condition a taste avoidance to saccharine in mice (McKay & Daniels ).…”
Section: Discussionmentioning
confidence: 68%
“…GLP-1 inhibition of water intake was first reported by Mads Tang-Christensen in 1996 [92] and was later confirmed by others [[755], [756], [757], [758], [759], [760]]. GLP-1 inhibition of water consumption is independent of food intake [758] and is blocked by pretreatment with exendin (9–39) [92].…”
Section: Glp-1 Effects On Water Intakementioning
confidence: 94%
“…Although the contributions of mechanoreceptors in the gut and hormonal signaling to the brain are well known to participate in the control of food intake, much less is known about the signals that affect fluid intake satiation. Some parallels seem to exist, however, and recent studies have shown that some of the same gut hormones that affect food intake also have effects on fluid intake (21,27,28,30,31,36,42). The role of feedback from the gut in the control of fluid intake, however, remains poorly understood.…”
mentioning
confidence: 93%